Implementation of cloud-based systems for integration in hotels - Nazarenko, Natalia (My University, 2015)
One of the biggest challenges for hotel operations has been the inability to integrate systems. Traditionally, there have been very few interface and integration standards for hotel technology providers. Hoteliers want to improve guest loyalty through technology purchase and as a result - the complexity and cost are compounded.
Keywords: interface; integration standards; hotel; інтерфейс; готель; інтеграція стандартів; интерфейс; интеграция стандартов; отель